Integrating IoT + Fog + Cloud Infrastructures: System Modeling and Research Challenges - Santos, Guto Leoni; Ferreira, Matheus; Ferreira, Leylane; Kelner, Judith; Sadok, Djamel; Albuquerque, Edison; Lynn, Theo; Endo, Patricia Takako (Fog and Edge Computing, 2019)
This chapter reviews the literature with regarding to the use of modeling techniques to represent and evaluate an integrated cloud‐to‐thing (C2T) system comprising cloud computing, fog computing, and the Internet‐of‐Things (IoT). It describes the methodology adopted to guide the literature review and provides a descriptive analysis of the final works selected for use in the chapter. The chapter presents an analysis of existing system modeling techniques used in cloud computing, fog computing, and IoT research against four categories, such as analytical models, Petri Net models, integer linear programming, and other approaches. It discusses the main scenarios modeled in extant research and the metrics used in evaluation. The chapter concludes with a discussion on research challenges and future directions for research. Future research may address the use of gateways to distribute/balance requests to be processed in the cloud infrastructure or by fog devices.